Movement Behavior of the Pine Needle Gall Midge (Diptera: Cecidomyiidae). Issue 5 (31st October 2020) - Liu, Huanxiu; Duan, Chunhua; Qi, Yukun; Ren, Lili; Wu, Haiwei
Abstract: The movement behavior of the pine needle gall midge ( Thecodiplosis japonensis Uchida Et Inouye (Diptera: Cecidomyiidae)), an invasive species in China, was determined by using a tethered flight technique and digital videography in the laboratory. The flight distance, duration, and speed of females were compared at different ages (2–10 h) and ambient temperatures (17, 21, 26, and 30°C). Female flight distance and duration at 26°C were significantly greater than those at 17°C and 21°C. The age of T. japonensis did not significantly affect the three flight characteristics. For females at 2–10 h of age at 26°C and 70% RH, the maximum flight distance was 667.59 m; the longest flight time was 6, 222.34 s; and the fastest flight speed was 0.44 m·s −1 . For larvae wetted with water, the highest jump was 5.7 cm; the longest jump was 9.6 cm; and the greatest distance moved in 5 min was 27.13 cm, which showed that the active dispersal potential of larvae was very low.